Provision of free ARV in public facilities in Tanzania : do the poor benefit? - Kahwa, Amos (Health Economics Unit, 2016)
The impact of the HIV pandemic in Tanzania has been profound and has affected all sectors. Today, HIV/AIDS is recognized not only as a major public health concern but also as social, economic and development problem in Tanzania as in most in Sub-Saharan African countries. With a population of estimated 37 million, Tanzania has an estimated of 2.5 million people infected with human immunodeficiency virus (HIV). The availability of antiretroviral therapy (ART) which has been defined as the main form of treatment (yet not a cure) for HIV/AIDS showed to significantly prolong and improve quality of life of people infected with HIV. By and large, the entire range of antiretroviral drugs is available anywhere in the world through private channels. Where resources permit, the supply may be adequate and consistent. Through the public sector, however, and for low-income patients, the choice of drugs may be somewhat restricted. This has implications for decisions such as when to start therapy, which therapeutic regimens to use, and what to do when treatment fails. The situation requires difficult choices in priority setting, poses serious ethical issues and imposes on government the obligation to scale up programmes in ways that are ethically sound, equitable, beneficial and sustainable as possible (WHO 2004). However in Tanzania, there is no clear policy established on targeting or prioritising specific population groups in order to avoid decision making based on subjective or arbitrary criteria that may lead to discrimination. The aim of this study was to establish the socioeconomic status of those individuals who benefit most from the provision of free ARV in terms of utilisation in urban and rural settings. It also aimed to identify the criteria used in enrolment of patients for free ARV provision, the barriers for ARV provision and patient's perception on ARV.